RSM-CCD design of volcanic ash/ rice husk ash based phosphate geopolymer for crystal violet adsorption: kinetics and isotherms - Armand Tchakounte; Idriss Lenou; Victor Shikuku; Ludovic Kemdjien; Joseph Dika; Charles Kede (Scientific Reports)
Abstract In this work, the application of central composite design (CCD) was used to optimise the synthesis of volcanic ash/ rice husk ash-based phosphate geopolymers. The effects of three factors namely, volcanic ash fraction, rice husk ash fraction and phosphoric acid concentration on porosity structure were investigated based on methylene blue index and iodine index as response variables. At optimized conditions of 3.72 g volcanic ash, 1.97 g rice husk ash and 5 M phosphoric acid concentration, desirable porosity structure was attained. The optimized geopolymer and their precursors were characterized by XRF, FTIR and XRD and applied to sequester crystal violet dye (CV) from water. The equilibrium data were described by the Langmuir isotherm with a maximum adsorption density of 14.6 mg/g. Adsorption rate followed pseudo-second-order kinetics. Notably, maximized porosity structure was attained at low acid concentration (5 M), a significant outcome in terms of cost and safety for pilot scale application.